1992
DOI: 10.1111/j.1432-1033.1992.tb17461.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the interaction of α subunits of GTP‐binding proteins with βγ dimers

Abstract: The interaction of several preparations of purified p;, dimers with two types of guanosinenucleotide-binding-regulatory-(G)-protein a subunits, a recombinant bvai3, made in Sf9 Spuduptern frugiperdu cells by the baculovirus (bv) expression system, and as, either purified from human erythrocyte G,-type GTP-binding protein, and activated by NaF/A1C13, or unpurified as found in a natural membrane, were studied. The By dimers used were from bovine rod outer segments (ROS), bovine brain, human erythrocytes (hRBC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…The amino-terminal region was identified to be important for interaction of Ga,-, Gas-Ga.-subunits with flydimers [32][33][34]. Furthermore, amino-terminal truncation of recombinant Gae3 reduced its affinity for ,y-dimers [23]. [40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino-terminal region was identified to be important for interaction of Ga,-, Gas-Ga.-subunits with flydimers [32][33][34]. Furthermore, amino-terminal truncation of recombinant Gae3 reduced its affinity for ,y-dimers [23]. [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose-density-gradient centrifugation was performed essentially as described previously [22,23]. Linear sucrose gradients [32P]NAD' was synthesized from [a-32P]ATP as described by Cassel and Pfeuffer [24].…”
Section: Sucrose Density Gradientsmentioning
confidence: 99%
“…Indeed, several different combinations of G ␤␥ subunits have been shown to interact with the same G ␣ in vitro (25). The sequence of the S. cerevisiae genome revealed only two G ␣ homologs (GPA1 and GPA2), but eight candidate ␤ genes and three candidate ␥ genes (26).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous biochemical (29,31,47,48) and mutational (49,50) studies have implicated the amino terminus of G protein ␣ subunits in the interaction with ␤␥ subunits. The resolution of the crystal structure of heterotrimeric G t (14) has confirmed that the amino-terminal helix of the ␣ t subunit is involved in forming a binding site for the ␤ t subunit.…”
Section: Fig 3 Identification Of ␣ T Proteolytic Fragments By Immunmentioning
confidence: 99%